A water-soluble eumelanin polymer with typical polyelectrolyte behaviour by triethyleneglycol N-functionalization. Issue 12 (29th January 2015) - Cicco, Stefania R.; Ambrico, Marianna; Ambrico, Paolo F.; Talamo, Maurizio Mastropasqua; Cardone, Antonio; Ligonzo, Teresa; Di Mundo, Rosa; Giannini, Cinzia; Sibillano, Teresa; Farinola, Gianluca M.; Manini, Paola; Napolitano, Alessandra; et al.
Abstract : Oxidative polymerization of 5, 6-dihydroxyindole N-functionalized with TEG chains as a new route to water-soluble eumelanin-like materials.. Abstract : N-functionalization of 5, 6-dihydroxyindole with a hydrophilic triethyleneglycol (TEG) chain provides access to a new class of water-soluble eumelanin-like materials with relatively high dielectric constant and polyelectrolyte behaviour, reflecting enhanced charge transport by in-depth incorporation of hydration networks.